Functional MR Imaging of the Human Cervical Spinal Cord - Madi, Saaussan (AJNR Am J Neuroradiol, 2001)
BACKGROUND AND PURPOSE: Although research with functional MR imaging of the brain has proliferated over the past 5 years, technical limitations, such as motion, chemical shift, and susceptibility artifacts, have impeded such research in the human spinal cord. The purpose of this investigation was to determine whether a reliable functional MR imaging signal can be elicited from the cervical spinal cord during simple motor activity. METHODS: Subjects performed three different motor tasks that activate different segments of the spinal cord. Gradient-echo-planar imaging on a 1.5-T clinical unit was used to image cervical spinal cords of human subjects. Another group of subjects was imaged while performing isometric exercise to study the relationship between the blood oxygenation level–dependent (BOLD) signal and applied force. RESULTS: Task-dependent BOLD activity was detected in all subjects. Signal amplitude varied between 0.5% and 7%. Moreover, a linear relationship was found between the applied force and the signal amplitude during isometric exercise. While regions of activation were distributed throughout the spinal cord, concentrated activity was found in the anatomic locations of expected motor innervation. CONCLUSION: The functional MR imaging signal can be reliably detected with motor activity in the human cervical spinal cord on a 1.5-T clinical unit. The location of neural activation has an anatomic correspondence to the myotome in use. The strength of the BOLD signal is directly proportional to the level of muscular activity.